The Singapore code of advertising practice and some proposals for reform. - Chan, Hiang Tiak. (2009)
The Singapore Code of Advertising Practice seeks to promote high standards of ethics in advertising by self-regulation against the background of national and international law, including the International Code of Advertising Practice published by the International Chamber of Commerce (ICC).